ANALISIS BENTUK MANAJEMEN PESERTA DIDIK DI SMTK ROTE TIMUR, KABUPATEN ROTE NDAO - Yonatan Foeh (Jurnal Dedikasi Pendidikan, 2023)
This study aims to determine the form of management of students at SMTK East Rote, East Rote District, Rote Ndao District. This research is classified as qualitative descriptive research with a case study type. The collection techniques used were observation sheets and interviews. Implementation of management forms is carried out through analysis of student planning, coaching and development of students, student evaluation, and student transfers. The results of the study showed that: First, the analysis of student planning showed that it had not been fully carried out by the school, which had not fully conducted an in-depth needs study related to the new student admission plan, as evidenced by not having a single document prepared by the school management starting from the board-teachers to the foundation. Second, coaching and developing students at this stage has been carried out through intra-curricular and extra-curricular activities. Third, evaluations of students the types of evaluation students receive at school include formative evaluation and summative evaluation. Fourth, student transfers: the school is open to students who want to make transfers, either incoming or outgoing transfers, but of course, there are several requirements that must be fulfilled by the student concerned..